Technological Innovations and Challenges in Banking Industry in India - Prof. Ch.Rajesham, V. Kanakalatha (International Journal of Scientific Research and Management (IJSRM), 2017)
Indian banking system touches the lives of millions of people and it is growing at a fast speed. Banking industry is facing number of challenges in India like changing needs and perceptions of customers, new rules from time to time and great advances in technologies. The pressure of meeting these challenges have forced banks to change the old ways of doing business. The research paper focuses on how the technology has changed the face of banking in India. India's banking system has seen some major (related to managing money) inventions of new things in the past at least 20 years which lead to huge/extreme improvements in banking services and operations. The different inventions of new things in banking and (related to managing money)part/area are ECS, RTGS, EFT, NEFT, Cash machine, Retail banking, Debit and Credit cards, free advice-giving services, online banking system, mobile banking and many more value added products and services. This paper also highlights the benefits and challenges of changing banking (popular things/general ways things are going). Banks are investing heavily in adoption of these inventions of new things. The need of hour is to design such a system that encourages the (wasting very little while working or producing something) of investment in inventions of new things and widens the gap between money/money income and costs involved with reference to (related to computers and science) up step.